Seed Production from Different Developmental Stages of Cabbage Post Vernalization - Červenski, Janko; Danojević, Dario; Adamović, Boris; Vlajić, Slobodan; Vojnović, Đorđe; Tošić, Ivana (Journal of Agricultural Sciences (Belgrade), 2026)
Cabbage is a biennial vegetable species and, as such, it requires vernalisation to transition from the vegetative to the generative phase. This study compared and analysed the quality and seed production after overwintering and vernalisation of cabbage in the open field at several developmental phenophases. The first treatment was carried out at the technologically mature head (TMH) formation phenophase of cabbage. The second treatment included cabbage plants at the fully-developed leaf rosette (LR) phenophase, while the third treatment included cabbage plants after the development of all rosette leaves and the removal of head leaves (OIS). In the first and third treatments, the plants overwintered in the ground, whereas in the second treatment, the plants were allowed to grow and develop naturally in the open field. Average total seed weight per plant (the main component in the seed production) varied between 26.0 g under the outer and inner stem treatment and 81.3 g under the fully developed leaf rosette treatment. As anticipated, this trait differed significantly across all three treatments. The fully developed leaf rosette treatment produced a markedly higher seed weight per plant compared with both the technologically mature head and outer and inner stem treatments.